Numerical studies of aluminum foam filled energy absorption connectors under quasi-static compression loading. (July 2017) - Wang, Yonghui; Zhai, Ximei; Wang, Wei
Abstract: Two type novel aluminum foam filled energy absorption connectors were proposed to be inserted between the blast resistant façade and building to absorb blast energy and reduce blast load transferred to the building. In this paper, the nonlinear finite element (FE) method was adopted to study the energy absorption performances of the two type connectors. The FE models of the connectors under quasi-static compression loading were first established and the accuracies of the FE models were verified by comparing the force–displacement curves obtained from tests and FE analyses. Then, the FE models were used to investigate the effects of filled aluminum foam, plate thickness and geometry as well as aluminum foam width on the energy absorption performances of the two type connectors. It was found that the two type connectors showed comparable energy absorption performances and the specific energy absorption could be significantly improved by filling the connector with aluminum foam. Highlights: Aluminum foam filled energy absorption connectors were numerically studied. The accuracy of the FE model was verified with test data and analytical prediction. Filled aluminum foam could improve the specific energy absorptions of connectors. The specific energy absorption of aluminum foam was higher than steel plate.